Formation of the concept of the socially responsible state as a factor of increasing the public governance and administration efficiency - Voronkova, V.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Fursìn, A. (My University, 2021)
EN: The urgency of the topic is due to the fact that today the importance of socially responsible state as a factor in overcoming instability and crisis in COVID-19, which requires reformatting the principles of public administration, survival of organizations and their adaptation to changes in uncertainty in the environment and needs constant modernization. To form the concept of a socially responsible state in COVID-19, it is necessary to overcome the conditions of crisis and instability, to create conditions for sustainable development, reset the management of public administration, to form new survival values of organizations at risk. The purpose of the study: theoretical and practical aspects of the concept the formation of socially responsible state as a factor in overcoming instability and crisis in COVID-19. Objectives of the study: 1. To study the formation of the concept of socially responsible state as a factor in overcoming instability and crisis in COVID-19. 2. To analyze the methodology of research of the socially responsible state as a factor of overcoming instability and crisis in the conditions of COVID-19. 3. To identify complexity as a sign of unstable and unbalanced public administration. 4. To identify the increasing complexity of organizations in modern conditions and the need for self-adaptation and self-regulation of systems. Research methodology. AGILE methodology acts as a system of new values, which extends to many areas of activity, including public administration and administration. Methods of synergetic analysis, including the theory of self-organizing open systems, which find themselves in points of imbalance, uncertainty, bifurcation (bifurcation), stochastic information (lack of information), system drift, resulting in a change of priorities. The result of the study. It is concluded that the state should realize and be responsible for its influence on society, promote socially responsible attitude to all processes taking place in society, for which to rebuild consciousness, principles and methods of activity that would be focused on obtaining social, economic and environmental effects that do not harm society and the environment. RU: Актуальность темы обусловлена тем, что сегодня повышается значение формирования социально-ответствен- ного государства как фактор преодоления нестабильности и кризиса в условиях COVID-19, что требует пере- форматирования основ публичного управления и администрирования, выживания организаций и их адаптации к изменениям в условиях неопределенности, которая происходит в окружающей среде и требует постоянной модернизации. Чтобы сформировать концепцию социально-ответственного государства в условиях COVID-19, следует преодолеть условия кризиса и нестабильности, создать условия устойчивого развития, перезагрузить управленческие основы публичного управления и администрирования, сформировать новые ценности выжи- вания организаций, которые находится в «ситуации риска». Цель исследования: теоретические и практические аспекты формирования концепции социально-ответственного государства как фактор преодоления нестабиль- ности и кризиса в условиях COVID-19. Задачи исследования: 1. Исследовать формирования концепции соци- ально-ответственного государства как фактор преодоления нестабильности и кризиса в условиях COVID-19. 2. Проанализировать методологию исследования социально-ответственного государства как фактор преодоления нестабильности и кризиса в условиях COVID-19. 3. Выяснить сложность как свойство нестабильного и несба- лансированного публичного управления и администрирования. 4.Виявить увеличение сложности организаций в современных условиях и необходимость самоадаптации и саморегулирования систем. Методология исследова- ния. AGILE-методология выступает как система новых ценностей, которые распространяются на многие сферы деятельности, в томе числе и на публичное управление и администрирование. Методы синергетического анализа включают теорию самоорганизационных открытых систем, которые оказываются в точках неравновесия, неопре- деленности, бифуркации (раздвоения), стохастичности информации (недостаток информации), дрейфа системы, в результате чего происходит смена приоритетов. Результат исследования. Сделан вывод, что государство должно осознать и нести ответственность за свое влияние на общество, способствовать социально-ответственному отно- шению ко всем процессам, которые происходят в обществе, для чего перестроить сознание, принципы и методы деятельности, которые были ориентированы на получение социального, экономического и экологического эффекта, которые не затрагивают общество и его отношение к окружающей среде. UK: Актуальність теми обумовлена тим, що сьогодні підвищується значення соціально-відповідальної держави як чинник подолання нестабільності та кризи в умовах COVID-19, що потребує переформатування засад публічного управління та адміністрування, виживання організацій та їх адаптації до змін в умовах невизначеності, що відбу- вається у навколишньому середовищі та потребує постійної модернізації. Щоб сформувати концепцію соціально відповідальної держави в умовах COVID-19, слід подолати умови кризи та нестабільності, створити умови ста- лого розвитку, перезавантажити управлінські засади публічного управління та адміністрування, сформувати нові цінності виживання організацій, які знаходиться у «ситуації ризику». Мета дослідження: теоретичні і практичні аспекти формування концепції соціально-відповідальної держави як чинник подолання нестабільності та кризи в умовах COVID-19. Завдання дослідження: 1. Дослідити формування концепції соціально-відповідальної дер- жави як чинник подолання нестабільності та кризи в умовах COVID-19. 2. Проаналізувати методологію дослі- дження соціально-відповідальної держави як чинник подолання нестабільності та кризи в умовах COVID-19. 3. З’ясувати складність як ознаку нестабільного і незбалансованого публічного управління та адміністрування. 4. Виявити збільшення складності організацій в сучасних умовах та необхідність самоадаптації та саморегулю- вання систем. Методологія дослідження. AGILE-методологія виступає, яка вис тупає як система нових ціннос- тей, що розповсюджується на багато сфер діяльності, у томі числі й на публічне управління та адміністрування. Методи синергетичного аналізу, що включають теорію самоорганізаційних відкритих систем, які потрапляють у точки нерівновагомості, невизначеності, біфуркації (роздвоєння), стохастичності інформації (не вистачає інфор- мації), дрейфу системи, у результаті чого відбувається зміна пріоритетів. Результат дослідження. Зроблено висно- вок, що держава повинна усвідомити і нести відповідальність за свій вплив на суспільство, сприяти соціально відповідальному ставленню до всіх процесів, що відбуваються у суспільстві, для чого перебудувати свідомість, принципи та методи діяльності, які б були орієнтовані на отримання соціального, економічного й екологічного ефекту, які не зашкоджують суспільству, людині і навколишньому середовищу.
Формирование концепции социально-ответственного государства как фактор повышения эффективности публичного управления и администрирования
Формування концепції соціально-відповідальної держави як чинник підвищення ефективності публічного управління та адміністрування
Keywords: concept of socially responsible state; instability; crisis; COVID-19; digitalization; концепция социально-ответственного государства; нестабильность; кризис; цифровизация; концепція соціально-відповідальної держави; нестабільність; криза; цифровізація